Nigeria's digital diaspora : citizen media, democracy, and participation - Kperogi, Farooq A., 1973- (Rochester studies in African history and the diaspora, 2020)
"In a disruptive media landscape characterized by the relentless death of legacy newspapers, Nigeria's Digital Diaspora shows that a country's transnational elite can shake its media ecosystem through distant online citizen journalism"--